Comparison of Effects of Salbutamol Inhalation with Continuous Positive Airway Pressure and Bubble Continuous Positive Airway Pressure Alone in the Management of Severe Transient Tachypnea of the Newborn - Afzal, Warda; Zaidi, Syed Taqi Hasan; Saba, Ameena; Shujaat, Wasif; Fatima, Benish; Maqsood, Almas (Pakistan Armed Forces Medical Journal, 2022)
Objective: To find the frequency of known risk factors in cases of severe transient tachypnea of the newborn (TTN) and to measure the effect of inhaled Salbutamol to bubble CPAP on required treatment duration.Study Design: Quasi-experimental study.Place and Duration of Study: Neonatal Intensive Care Unit, Combined Military Hospital, Malir Cantt, Karachi Pakistan, from Nov 2019 to Jun 2020.Methodology: A total of 60 cases of severe TTN, labelled on a predefined criterion were included in the study. The sample was randomized into two groups using an alternate sampling technique. Group-A was treated with bubble CPAP alone, while in Group-B, inhaled Salbutamol was added. The response was measured regarding the time taken to settle respiratory distress.Results: Out of 60 cases, 54(90.0%) were delivered through Caesarean section. A total of 9(15.0%) cases were born prematurely. Polycythemia was found in 10(16.6%) cases. Maternal asthma and gestational diabetes frequency were 8(13.33%) and 12(20.0%), respectively. A significant reduction was seen in the duration of respiratory distress in the study population receiving bubble CPAP with inhaled Salbutamol in the first 24 hours of illness (p-value